The Effect of Workload and Work-Family Conflict on the Performance of Employees of production Laboratory I & III PT Petrokimia Gresik - Firmana, Gumilar Alin; Rahayuningsih, Idha; Wicaksono, Awang Setiawan; Sholicah, Ima Fitri; Amelasasih, Prianggi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The decrease in subject performance is characterized by error in writing reports, reporting of late analysis results, and lack of care in work. This study aims to determine the effect of workload and work family conflict on the performance of employees of the production laboratory I and III of PT Petrokimia Gresik. The type of research used is quantitative with a causal correlation type, validity and reliability testing using the validity of the content and the reliability of the consistency of the combined grains. The population used in this study was 85 people. The sampling technique used was saturated sampling of 85 people. The research measuring instruments are compiled based on theories from Koopmans for performance, Reid & Nygren for workloads, and Greenhaus & Beutell for work family conflict using a Likert scale with 5 answer choices. The data analysis technique used is a multiple linear regression test. The results of this study show that workload & work family conflict has a simultaneous influence on performance. The subjects in this study had the categories of medium performance, medium workload, and moderate level of work family conflict. Based on these results, it was found that there was a negative influence between workload and work family conflict on performance.